Modeling and control performance of a negative stiffness damper for suppressing stay cable vibrations. Issue 4 (12th October 2015) - Zhou, Peng; Li, Hui
Summary: A negative stiffness damper (NSD) is proposed, and its performance on suppressing stay cable vibrations is investigated by numerical simulations and experimental tests. First, the NSD consists of two pressed springs and an oil damper. The two pressed springs are attached perpendicularly to the piston rod of the oil damper in symmetrical configuration. Mechanical model of this damper is derived according to the geometrical configuration and validated experimentally. Considering the simplified model of single‐mode vibration of a cable, the cable frequency with the NSD is investigated theoretically by average method, and the lower limit on the pressed degree of two springs is proposed. Numerical examples of cable with NSD and oil damper under sinusoidal excitations are conducted. The NSD shows the superior reduction performance of both amplitudes in time history and peak values of frequency response. A series of single‐mode and multi‐mode cable vibration control experiments are carried out to evaluate mitigation performance achieved by the NSD. The results indicate that this NSD can provide larger additional modal damping ratio to the cable regardless of single‐mode and multiple‐mode vibration. Thus, this NSD achieves further reduction of the cable than the oil damper through negative stiffness behavior, instead of complex active or semi‐active devices with real‐time feedback. Copyright © 2015 John Wiley & Sons, Ltd.